Protein-A immunoadsorption combined with immunosuppressive treatment in refractory primary Sjögren’s syndrome coexisting with NMOSD: a case report and literature review - Fan, Wei; Chen, Xuyan; Xiao, Pingping; Wei, Bo; Zhang, Yi; Huang, Jinmei; Wu, Shufan; Lu, Liangjing (Frontiers in Immunology, 2024)
The treatment of primary Sjögren's syndrome (pSS) coexisting with neuromyelitis optica spectrum disorder (NMOSD) using protein-A immunoadsorption combined with immunosuppressive therapy has rarely been reported. Herein, we present the case of a 35-year-old female diagnosed with pSS concomitant with NMOSD (pSS-NMOSD) who demonstrated a positive response to protein-A immunoadsorption after failing to respond to therapy comprising high-dose intravenous methylprednisolone (IVMP) and intravenous immunoglobulin (IVIG). Within one week of receiving three sessions of immunoadsorption combined with immunosuppressive treatment, the patient's clinical symptoms (blurred vision, paraparesis, and dysfunctional proprioception) significantly improved. Additionally, a rapid decrease in circulating levels of Aquaporin-4 immunoglobulin G antibodies (AQP4-IgG), immunoglobulin (Ig) A, IgG, IgM, erythrocyte sedimentation rate (ESR), and rheumatoid factor (RF) were observed. Magnetic resonance imaging (MRI) further revealed a significant reduction in lesions associated with longitudinal extensive transverse myelitis. During the follow-up period, prednisolone was gradually tapered to a maintenance dose of 5-10 mg/day, whereas mycophenolate mofetil (MMF) was maintained at 1.0-1.5 g/day. The patient's condition has remained stable for four years, with no signs of recurrence or progression observed on imaging examination. Therefore, this case suggests that protein A immunoadsorption may represent a potentially effective therapeutic option for patients with pSS-NMOSD who are refractory to conventional treatments.